Policy Analysis Regarding The Maintenance Of Religious Harmony And The Establishment Of Houses Of Worship (Implementatation Study of the Joint Regulation of Minister of Religion And Home Affair Minister Number 9/8 of 2006 in Cilegon City, Banten Province) - Imam Rozikin; Ermaya Suradinata; Deti Mulyati; Mansyur Achmad (Eduvest - Journal of Universal Studies, 2024)
Indonesia, as a large country in the Asian region, is characterized by thousands of islands, a population of hundreds of millions of people, and various ethnicities, races and religions. However, behind this diversity it can also be a trigger for conflict, both internal and external. One aspect that is often highlighted is the role of religion in conflicts between religious communities. Joint Regulation of the Minister of Religion and the Minister of Home Affairs Number 9/8 of 2006 concerning the Establishment of Houses of Worship was established to regulate procedures for building places of worship, including construction, maintenance and management. However, the implementation of these regulations in the field often faces various challenges and obstacles. The research reviews the implementation of these regulations in the City of Cilegon, Banten. The review presented relate to the licensing context, the concept of religious harmony, and the concept of establishing places of worship. The method used is qualitative research with literature study as a data acquisition technique. The research results show that the implementation of the Joint Regulation of the Minister of Religion and the Minister of Home Affairs Number 9/8 of 2006 concerning the Establishment of Houses of Worship in Cilegon City has not been fully effective. Socialization efforts, improving regulations, and enforcing government neutrality are the main keys in increasing the effectiveness of implementing these regulations.